GLOBAL ECONOMIC POLICY FOR THE MODERN WORLD ECONOMY - Klodt, Henning (Journal of European Economy, 2018)
The author elaborates the criteria which may be applied in a number of economic policy areas that are in the spotlight international policy debate.